2‐O‐Acetyl‐3, 4, 5, 6‐tetra‐O‐benzyl‐d‐myo‐inosityl diphenylphosphate: A new useful intermediate to inositol phosphate and phospholipids. Issue 8 (9th May 2022) - Sangiorgio, Sara; Cambò, Mattia; Semproli, Riccardo; Ubiali, Daniela; Speranza, Giovanna; Rabuffetti, Marco
Abstract: Inositol phosphates and inositol phospholipids are ubiquitous in biochemistry and play a central role in cell signaling and regulation events. For this reason, their synthesis has attracted widespread interest. This paper describes the preparation of a new optically active inositol phosphate derivative, 2 ‐O‐ acetyl‐3, 4, 5, 6‐tetra ‐O‐ benzyl‐d ‐ myo ‐inosityl diphenylphosphate (6 ), and its characterization by spectroscopic methods. Compound (6 ) represents a useful intermediate for the preparation of inositol phosphate and phospholipids, in particular of glycerophosphoinositol (GPI), a natural anti‐inflammatory agent. Abstract :